Peningkatan Kemampuan TOEFL melalui Pelatihan Intensif untuk Siswa Kelas 12 SMAS NW Ulil Albab Gegek: Enhancing TOEFL Proficiency through Intensive Training for Twelfth Grade Students at SMAS NW Ulil Albab Gegek - Herman Supriadi; Lalu Budi Karyawan; Muhammad Fahrurrozi (Universitas Hamzanwadi, 2024)
Language is an important communication system, and English serves as an international language and a requirement for studying abroad. However, students in Islamic boarding schools often lack time to learn English. To address this, SMAS NW Ulil Albab Gegek initiated a TOEFL training program for twelfth-grade students from August to October 2023. This program involved three main skills: reading, writing, and listening, with sessions held three times a week without disrupting the students' regular schedules. The preparation stage included planning materials, scheduling, and initial observations, followed by student registration with parental consent. The implementation used the school's laboratory, with pre-test and post-test evaluations to measure progress. Results showed an increase in students' TOEFL scores from an average of 383 (pre-test) to 421 (post-test), reflecting a 5% improvement. Although the score increase was modest, it demonstrated the training's effectiveness in enhancing students' understanding and test-taking strategies. This program not only prepared students for higher education and scholarship opportunities but also improved their overall English proficiency. The initiative by SMAS NW Ulil Albab Gegek provides a model for integrating intensive TOEFL training into the school curriculum, especially in remote areas, thus enhancing students' academic and professional prospects